2017
DOI: 10.1016/j.psyneuen.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis genetic variation and early stress moderates amygdala function

Abstract: Early life stress may precipitate psychopathology, at least in part, by influencing amygdala function. Converging evidence across species suggests that links between childhood stress and amygdala function may be dependent upon hypothalamic-pituitary-adrenal (HPA) axis function. Using data from college-attending non-Hispanic European-Americans (n=308) who completed the Duke Neurogenetics Study, we examined whether early life stress (ELS) and HPA axis genetic variation interact to predict threat-related amygdala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…The current study exhibited several strengths including the use of a theoretically-derived, biological pathway based MGPS established in previous research (Di Iorio et al, 2017), semi-structured life stress interview assessments, and a multi-wave prospective study design. However, there were also some limitations which should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study exhibited several strengths including the use of a theoretically-derived, biological pathway based MGPS established in previous research (Di Iorio et al, 2017), semi-structured life stress interview assessments, and a multi-wave prospective study design. However, there were also some limitations which should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a MGPS approach focusing on the combined influence of polymorphisms in genes known to affect HPA axis functioning ( CRHR1 , FKBP5 , and NR3C2 ). We chose to focus specifically on these three genes due to their known influence on HPA axis functioning and to replicate a previously established, theoretically and biologically-driven MGPS utilized in previous research (Di Iorio et al, 2017). 1 As noted earlier, the MGPS approach is consistent with recent research highlighting the importance of examining the aggregate influence of multiple SNPs as opposed to examining candidate genes in isolation (Nikolova et al, 2011; Owens et al, 2016; Pagliaccio et al, 2014).…”
Section: The Current Studymentioning
confidence: 99%
“…Further, HPA axis relevant SNPs moderate the effects of early life stress exposure. In particular, neural ecophenotypes of early life stress (increased amygdala volume, increased reactivity to emotional stimuli, and decreased connectivity with prefrontal regions) are more pronounced in individuals with a genetic disposition towards greater HPA axis activity (Di Iorio et al, 2017;Holz et al, 2015 , 2015a, 2014White et al, 2012). Similarly, SNPs conferring greater HPA axis activity might also moderate the impairments of emotion recognition following ELS.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm infants who experienced more painful procedures had significantly elevated cortisol levels when they were school-aged (Brummelte et al, 2015). It has also been demonstrated that early life stress can alter HPA and amydgalar activity in humans (Heim & Nemeroff, 2002;Iorio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%